Clinical features and risk factors of acute kidney injury following bee stings - LI Fu-gang; LIU Li; ZHANG Yong; LU Feng; CHEN Tao; WANG Gang; LUO Zhi-gang; CHEN De-zheng (Linchuang shenzangbing zazhi)
Objective To retrospectively analyze the clinical features and risk factors of acute kidney injury( AKI) following bee stings. Methods A retrospective study was conducted on patients with suspected bee stings in People ’s Hospital of Jianyang from September 2014 to September 2016. The patients were divided into AKI group and non-AKI group according to the occurrence of AKI. The clinical and laboratory data were collected and the risk factors were analyzed by logistic regression. Results Sixteen cases(9. 75%) suffered AKI in 164 patients. There was no statistically significant difference between the two groups in the extent of the sting,the type of bee and history of cardiovascular diseases. The bee stings mainly occurred during 6:00 to 12:00(46. 95%),87(53. 04%) during July to September and 62(37. 8%)during October to December. The clinical manifestations after bee stings included skin rash,headache/dizziness,dyspnea,nausea/vomiting,palpitation,chest tightness and consciousness,showing no statistically significant difference between two groups. The gross hematuria was significantly higher in AKI group than in non-AKI group( P < 0. 01). The laboratory examination results of two groups were statistically different. The results of logistic regression analysis showed that gross hematuria( OR = 8. 623,95% CI 1. 656-44. 919,P= 0. 011),lencocyte > 20 ×10~9/L( OR = 37. 689,95% CI 4. 149-342. 363,P = 0. 001),and cTnI > 100ng/L( OR = 5. 718,95% CI 1. 100-29. 716,P = 0. 038) were the independent risk factors of AKI in patients with bee stings. Conclusions Bee stings should focus on whether gross hematuria,blood monitoring and high-sensitivity troponin,give blood purification treatment as soon as possible,to reduce the death rate.